Features of Cerebral Hemorrhage in the Victims of Peaceful Territory and Fighters of the Operation of the Combined Forces – of the Antiterrorist Operation After Traumatic Brain Injury of Mild Severity in Acute, Intermediate and Distant Periods - V. Shevaga; M. Semchyshyn; B. Zadorozhna; A. Zadorozhny (Львівський клінічний вісник)
Introduction. Craniocerebral trauma determines its place among the priority areas of modern clinical neurology. Brain injuries along with dystrophic processes cause disorders of cerebral hemodynamics and vascular tone, which are significant and are important factors in the pathogenesis of neurological symptoms after trauma. The severity of the injury is not always associated with the degree of changes in blood flow, but the incidence and mortality from cerebrovascular lesions increase after trauma received during hostilities, because the vascular system of the brain is too sensitive to mechanical influences and different energies (light, sound, temperature, electromagnetic), which are released during the explosions of mines or shells. To substantiate the relevance of the study, it is important to evaluate the study of cerebral hemodynamics as a basis for pathogenetically sound correction of cerebral blood flow disorders and the creation of a diagnostic complex in mild trauma in acute, intermediate and distant periods in the examined patients. The aim of the study. To study the features of cerebral blood flow in the victims of peaceful territory and fighters of the operation of the combined forces (OCF) – of the antiterrorist operation (ATO) after traumatic brain injury of mild severity in acute, intermediate and distant periods. Materials and methods. We examined with brain injury 262 persons of peaceful territory (concussion of 143 persons, contusion of the brain injury of mild severity 119 persons) and 204 fighters of the OCF – of the ATO (concussion of 144 fighters, contusion of the brain injury of mild severity 60 fighters).The age of the persons of peaceful territory was from 18 to 55 years, and the fighters of the OCF – of the ATO from 20 to 55 years. Study of blood flow in cerebral vessels was performed in acute (5 – 10 days), intermediate (20 – 30 days) and distant periods (after 2 years) trauma. The control group consisted of 20 practically healthy persons. Cerebral flow was studied in the intracranial departments of both internal carotid arteries and both average cerebral arteries, which form the largest blood supply zone. For differentiation of conditions hyperemia – vasospasm we defined hemispherical index, as the ratio of maximal systolic frequency in the middle cerebral and internal carotid arteries, which allowed us to evaluate the severity of cerebral angiospasm. Results. Analysis of the results of the study showed that cerebral hemodynamic disorders occurred in cerebral vessels with brain injury of mild severity. Asymmetry and bleeding disorders were more pronounced on the traumatic side. We observed more pronounced changes in the operation of the combined forces of the ATO combatant groups in comparison with persons of peaceful territory. Let´s assume, that the state of constant voltage and stressogenic factors influenced blood flow in the vessels of the brain, and therefore the trauma with its constantly in the fighters proceeded in accordance with the unlike the victims of peaceful territory. Conclusions. The dependence between the indicators of the blood brain and the degree of severity of the injury was found, the greater degree of traumatic lesion, the more significant were the changes in cerebral hemodynamics.